2017
DOI: 10.3414/me17-01-0024
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Emergency Department Hospital Admission Based on Natural Language Processing and Neural Networks

Abstract: The predictive accuracy of hospital admission or transfer for patients who presented to ED triage overall was good, and was improved with the inclusion of free text data from a patient's reason for visit regardless of modeling approach. Natural language processing and neural networks that incorporate patient-reported outcome free text may increase predictive accuracy for hospital admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 62 publications
1
71
0
Order By: Relevance
“…However, modern machine learning approaches possess scalability within a larger context of health information technology (eg, extracting a multitude of potential predictors from electronic health records and monitoring devices, continuous sophistication of the model using updated health data, and reinforcement learning). 55 , 56 Indeed, the machine learning approaches have demonstrated potential to further improve their performance by integrating recently developed algorithms, such as natural language processing 57 , 58 and diagnostically relevant facial gestalt information from images. 59 Our observations and these recent developments collectively present reason for cautious optimism that machine learning approaches, as an assistive technology, further enhance the clinician’s triage decision making in a large ED population of children.…”
Section: Discussionmentioning
confidence: 99%
“…However, modern machine learning approaches possess scalability within a larger context of health information technology (eg, extracting a multitude of potential predictors from electronic health records and monitoring devices, continuous sophistication of the model using updated health data, and reinforcement learning). 55 , 56 Indeed, the machine learning approaches have demonstrated potential to further improve their performance by integrating recently developed algorithms, such as natural language processing 57 , 58 and diagnostically relevant facial gestalt information from images. 59 Our observations and these recent developments collectively present reason for cautious optimism that machine learning approaches, as an assistive technology, further enhance the clinician’s triage decision making in a large ED population of children.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches offer advantages in that they account for high-order, non-linear interactions between predictors and gain more stable prediction [17]. Recent studies have reported that the application of machine learning models may provide high predictive ability at ED triage in selected patient populations and settings—e.g., children [18], patients with asthma and COPD exacerbation [19], and in few urban EDs [11, 20, 21]. Despite this clinical and research promise, no study has yet examined the utility of modern machine learning models for predicting clinical outcomes in a large population of adult patients in the ED.…”
Section: Introductionmentioning
confidence: 99%
“…The number of actual and predicted outcomes of prediction models, according to the score of the reference model. www.nature.com/scientificreports/ and reinforcement learning [21][22][23][24] . In the past, this scalability had not been attainable with the use of conventional approaches.…”
Section: Discussionmentioning
confidence: 99%